In-house phage amplification assay is a sound alternative for detecting rifampin-resistant Mycobacterium tuberculosis in low-resource settings - Simboli, Norberto (2005)
Fil: Simboli, Norberto. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.